2018
DOI: 10.1080/03670244.2018.1492381
|View full text |Cite
|
Sign up to set email alerts
|

Parental correlates of food parenting practices: socioeconomic status, weight, and dieting status

Abstract: Little research has considered how parents' socioeconomic indicators, body mass index (BMI), and dieting status relate to their food parenting. The current study used self-report data from parents of young children to examine group differences on three types of food parenting practices (Structure, Coercive Control, and Autonomy Promotion). Few group differences were found for socioeconomic indicators. However, parent dieting status moderated effects of parent BMI on structure and autonomy promotion. Obese, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Apart from rules and limits which was assessed in two studies, the structure FPPs described above were all examined in single, unreplicated studies. With regards to unstructured FPPs, the evidence was inconclusive due to contradictory study results [67,69,73,85].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from rules and limits which was assessed in two studies, the structure FPPs described above were all examined in single, unreplicated studies. With regards to unstructured FPPs, the evidence was inconclusive due to contradictory study results [67,69,73,85].…”
Section: Discussionmentioning
confidence: 99%
“…The oldest studies included in the review were published in 2001 [67,68] and the most recent studies were published in 2018 [65,69] (Table 1: Study Results Table can be found in supplementary materials, S1). Of the twenty relevant studies, sixteen were cross-sectional [67,68,[70][71][72][73][74][75][76][77][78][79], three were observational [80][81][82], and one longitudinal [83].…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations